MASYARAKAT LUNTO TIMUR DAN KONGSI KEMATIAN - Walan Yudhiani; Azizah Fitrah (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The issue of organizing a corpse is the most important issue that must be considered by every Muslim, because organizing a corpse is a kifayah obligation for the living. Likewise, the people of East Lunto, Sawah Lunto Regency, where the implementation of the remains of men is carried out by the Malin tribe. As for the remains of women carried out by Mrs. Anis. So it is not uncommon for bodies to be held too late especially for the bodies of women because the organizers are not yet present or cannot be present. For this reason, several strategies are carried out so that this problem can be overcome. The categories used are (1) lectures, (2) discussions, (3) mentoring. Based on the results of assistance to the people of East Lunto, Sawah Lunto Subdistrict, currently, the East Lunto community already has a death joint organization so that the bodies can be held quickly and in accordance with the guidance of the Prophet Muhammad.